Effects of hydrostatic pressure on matrix synthesis in different regions of the intervertebral disk. - Ishihara, H; McNally, D; Urban, J; Hall, A (1996)
The intervertebral disk is routinely subjected to compressive loads that alter with posture and muscle activity and can produce pressures > 2 MPa in human lumbar disks in vivo (A. Nachemson and G. Elfstrom. Scand. J. Rehabil. Med. 2, Suppl. 1:1-40, 1979; A. Nachemson and J. M. Morris. J. Bone Jt. Surg. Am. Vol. 46A: 1077-1092, 1964). We measured the effect of load on hydrostatic pressures in bovine caudal disks. With increase in applied load, pressure increased linearly in the nucleus and inner annulus. The resting pressure measured after slaughter (0.19 +/- 0.05 MPa) and the pressure at failure (34 MPa, estimated from the vertebrae/disk segment failure load of 7,430 +/- 590 N) define the limits that can occur in vivo. Because hydrostatic pressure influences matrix synthesis in articular cartilage, we have examined the effects of pressures in the range 1-10 MPa applied for 20 s or 2 h on proteoglycan synthesis in bovine caudal and human lumbar intervertebral disks in vitro. In the nucleus pulposus and inner annulus of bovine disks, application of hydrostatic pressure in the range of 1-7.5 MPa for only 20 s stimulated matrix synthesis over the following 2 h at atmospheric pressure. The maximum stimulation in the bovine disks was seen in the inner annulus after application of 2.5 MPa, where proteoglycan synthesis rates doubled. Exposure to 2.5 MPa also stimulated synthesis in the nucleus pulposus of human disks taken at surgery, whereas 7.5 MPa inhibited synthesis in five out of six specimens. With 2-h continuous exposure to the same levels of pressure, no stimulation was seen in the nucleus of bovine disks, and significant stimulation was only observed at 5.0 MPa in the inner annulus. Exposure to 10 MPa for either 20 s or 2 h inhibited proteoglycan synthesis in these regions of the disks. In contrast, in the outer annulus, where loading does not lead to a rise in hydrostatic pressure in vivo, there was no significant response to hydrostatic pressure over the range of 1-10 MPa in bovine or human disks.